The Role of Consumer Ethnocentrism, Perceived Quality, Perceived Price, and Perceived Brand Image on Willingness to Buy Erigo Clothing - Ciu, Edgar; Wijayanti, Cynthia Anna (Faculty of Economics and Business, Universitas Klabat, 2024)
The initial survey findings revealed that Indonesian consumers prefer supporting local brands but are reluctant to purchase them if the prices exceed those of foreign brands. Additionally, they are open to foreign brands effectively marketed in Indonesia. This study examines and analyzes the impact of consumer ethnocentrism, perceived quality, perceived price, and perceived brand image on the willingness to purchase Erigo apparel. Employing a quantitative approach, the study used PLS-SEM as the data analysis method with SmartPLS software. Non-probability purposive sampling was utilized to gather responses from 192 participants via Google Forms. The study uncovered a positive and significant influence of consumer ethnocentrism, perceived price, and perceived brand image on the willingness to buy Erigo apparel. However, perceived quality had a positive but statistically non-significant impact on this willingness. The managerial contribution includes Erigo's leveraging consumer ethnocentrism by promoting local craftsmanship and cultural diversity, enhancing its pricing strategy to reflect value, and strategically building a positive brand image to stand out against foreign competitors. Focused campaigns, fair pricing, and active social media engagement can significantly boost consumer interest in purchasing Erigo clothing.